Media Pembelajaran Dalam Perspektif Pendidikan Islam (Tazakka: Jurnal Pendidikan dan Keislaman, 2023)
Learning media is one of the components that must be possessed in the education system. In the process of media learning it functions as an intermediary for educators in conveying science so that students better understand the material presented. The use of learning media must be adapted to Islamic values so that it will make it easier to achieve educational goals. This research aims to describe how media learning is in the perspective of Islamic education. The research method used is a qualitative research method with a library study approach. All data is taken from various sources from the koran, books, theories and opinions of experts. To make this research more interesting, all themes from the results of the study will be discussed based on ancient research and current Islamic education issues. The results of this study explain that learning media from an Islamic perspective must follow the times by the Islamic values taught by Rasulullah Saw
Keywords: Learning Media; Islamic Education; Islamic Values